The Relevance of Regional Autonomy in Human Resource Empowerment to Achieve Good Governance: A SWOT Analysis Study - Rahmatulloh, Aang; Purwanto; Dahlan, Charly; Inayatullah, Muhamad Iqbal; Sri Mulyani (Jurnal Economic Resource, 2022)
Regional autonomy grants extensive authority to local governments to manage human resources (HR) as part of efforts to achieve good governance. However, its implementation still faces challenges such as HR capacity gaps, budget constraints, and the influence of globalisation. This study aims to analyse the relevance of regional autonomy in HRD to strengthen the principles of good governance and formulate appropriate development strategies. This study uses a descriptive qualitative method with a SWOT analysis approach. Primary data were obtained through in-depth interviews and observations in several local governments selected purposively based on criteria of active HRD programmes. Secondary data were collected from official government documents, publications from the Central Statistics Agency, and relevant policy reports. The analysis was conducted using the Miles and Huberman model, which includes data reduction, data presentation, and conclusion drawing, while data validity was ensured through triangulation of sources and methods. The results indicate that the success of good governance is highly dependent on the quality of human resources and an adaptive bureaucratic structure. Strengths include local autonomy, demographic potential, and regulatory support, while weaknesses include disparities in human resource quality and limited performance evaluation. The greatest opportunities lie in the utilisation of digital technology and strategic partnerships, while threats include brain drain and inconsistent regulatory changes. The implications of this study emphasise the importance of an integrated strategy that combines human resource capacity building, technology utilisation, and national character building as instruments of national power in facing the challenges of globalisation.